A dependable and lightweight trust proliferation approach for the collaborative IoT systems. (2018) - Benkerrou, Hayet; Omar, Mawloud; Bouchebbah, Fatah; Mouhoub, Younes Ait
Trust and reputation evaluation in the internet of things (IoT) constitutes nowadays a major challenge that is still attracting the research community to work on and investigate. The IoT with its widely heterogeneous objects requires collaborative computation to perform heavy cryptographic operations in the most constrained resource devices. Indeed, the effectiveness of the trust and reputation assessment plays an important role for selecting the best collaborators. In this paper, we propose a dependable and lightweight trust proliferation approach for the collaborative IoT systems. By recording the malicious tasks which could be performed during the service execution, our approach introduces a new derivation of direct trust. Furthermore, it combines dynamically the direct and indirect trust evaluation to ensure more trustworthiness and reliability in the selection of the best collaborator objects. Through the simulations, we show that our trust derivation approach achieves high accuracy in the selection of efficient and confident collaborators.